2018
DOI: 10.1016/j.pscychresns.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Reduced subcortical volumes among preschool-age girls and boys with ADHD

Abstract: Anomalous brain structure and function are implicated in children with attention-deficit/hyperactivity disorder (ADHD). Most neuroimaging research, however, has examined school-aged children, despite the typical onset of symptoms in early childhood. This study compared the volumes of subcortical structures (caudate nucleus, putamen, globus pallidus, and thalamus) among preschoolers with ADHD and typically developing (TD) children. High resolution T1-weighted 3D MPRAGE images covering the whole brain were acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 51 publications
4
22
1
1
Order By: Relevance
“…Thus, it may be that motor deficits and the associated anomalies in basal ganglia morphology may be more apparent among boys with ADHD during this developmental period whereas girls with ADHD may show similar anomalies compared to TD girls at a younger or older age depending on the brain region. This pattern is supported by findings from our recent study of preschoolers with and without ADHD, showing reduced volume of the caudate, globus pallidus, and thalamus among girls with ADHD compared to TD girls whereas no significant diagnostic differences were observed among boys [74]. …”
Section: Discussionsupporting
confidence: 78%
“…Thus, it may be that motor deficits and the associated anomalies in basal ganglia morphology may be more apparent among boys with ADHD during this developmental period whereas girls with ADHD may show similar anomalies compared to TD girls at a younger or older age depending on the brain region. This pattern is supported by findings from our recent study of preschoolers with and without ADHD, showing reduced volume of the caudate, globus pallidus, and thalamus among girls with ADHD compared to TD girls whereas no significant diagnostic differences were observed among boys [74]. …”
Section: Discussionsupporting
confidence: 78%
“…We found a significantly weaker negative correlation between BOLD signals in the caudate and reward waiting time in ADHD. Previous structural MRI studies have indicated a reduction in caudate volume in children with ADHD . A voxel‐based meta‐analysis showed a reduction in caudate volume in individuals with ADHD that was more evident in children than in adults .…”
Section: Discussionmentioning
confidence: 89%
“…Previous structural MRI studies have indicated a reduction in caudate volume in children with ADHD. 29,30 A voxel-based meta-analysis showed a reduction in caudate volume in individuals with ADHD that was more evident in children than in adults. 31 A previous fMRI study reported reduced BOLD signals during an attentional task in adults with ADHD, 32 and a meta-analysis of fMRI studies showed that stimulant medication might normalize caudate activity.…”
Section: Discussionmentioning
confidence: 99%
“…However reduced brain volumes of the hippocampus, caudate, putamen, thalamus, insula and prefrontal cortex are also shown in adults with heart failure [34,35]. Furthermore such brain "injuries" were also shown in children with attention deficit hyperactivity disorder [36] and children with low birth weight due to small for gestational age syndrome [37]. Most of these brain structures are parts of the so called central autonomic network and limbic system.…”
Section: Magnet Resonance Imaging and Neurocognitive Impairmentmentioning
confidence: 99%